(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Strategic networking represents firm’s strategic posture to develop long-term and sustainable business relationships with the aim of focusing on core business activities and gaining additional benefits from profound coopetitional relations with various market players. The purpose of this paper is to examine the impact of strategic networking (SN) on the performance of Croatian manufacturing SMEs where unidimensional and multidimensional analysis has been performed. In order to reveal more comprehensive understanding of SN-performance relationship, financial as well as non-financial performance indicators were tested. Moreover, moderating influence of external environment was used to further explore SN-performance relationship. While unidimensional analysis exhibits positive effects of SN on business performance, only reputation as an antecedent of SN in multidimensional analysis confirms the existence of such a positive relationship. Thus, the overall results can be considered inconclusive as to the existence, strength, and direction of the effect of the observed variables. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.